ANALYSIS OF DOMINANT FACTORS AFFECTING QUALITY PERFORMANCE ON HOUSING PROJECTS IN BANYUWANGI REGENCY - Gilang Id’fi, Umi Mutoharoh (Universitas Negeri Malang, 2021)
Abstract: During ten years the population increased by 32.56 million people. The backlog figure in 2015 was 11.5 million housing units. The demand for housing increases annually by 1.46 million while the supply capacity is 400 thousand housing units. So, there is still a gap of 1.06 million units per year. This gap is a backlog that will increase every year if housing development cannot keep up with the demand for housing. The development of the real estate sector in Banyuwangi is experiencing constant growth. In 2012, the real estate sector grew by 7.11% and then rose to 8.30% in 2013. In 2014 the real estate grew by 9.79%. Housing continues to develop as seen from the number of housing areas until 2018 around 204 locations. The increase in the number of developers in Banyuwangi Regency has not been accompanied by an increase in performance. As happened in the Bumi Emas Residence Housing, it did not match the working drawings. The purpose of this study is to describe the dominant factors that affect the performance of housing quality. As well as describe the factors that affect the quality performance in luxury, medium, and simple housing types. The design of this research is to use the type of quantitative descriptive research. The method used is AHP (Analytical Hierarchy Process) with the help of Expert Choice 11 software. Primary data was obtained from distributing questionnaires. The population in this study is the staff of luxury type housing developers, medium type housing developers, Bumi Emas Residence developers or simple type housing. Determination of research samples using purposive sampling technique. So that the number of samples was determined by 39 staff developers. Respondents in this study were directors, commissioners, financial staff, technical staff, field supervisors, foreman. Based on the results of data analysis, it is concluded that the dominant factor affecting quality performance in housing projects is the human resource factor. Factors that affect the type of luxury housing is human resources. Factors that affect the quality performance of the medium type housing is the implementation method. Factors that affect the quality performance of simple type housing is the work environment factor. Keywords: Quality Performance, Housing Project, Analytical Hierarchy Process